Effects of long-term antiretroviral therapy in reproductive-age women in sub-Saharan Africa (the PEPFAR PROMOTE study): a multi-country observational cohort study. Issue 6 (June 2022) - Taha, Taha E; Yende-Zuma, Nonhlanhla; Brummel, Sean S; Stranix-Chibanda, Lynda; Wambuzi Ogwang, Lillian; Dadabhai, Sufia; Chinula, Lameck; Nyati, Mandisa M; Hanley, Sherika; Makanani, Bonus; Chipato, Tsungai; Atuhaire, Patience; et al.
Summary: Background: We report the long-term impact of ART in women of reproductive age (15–49 years) in Africa who have been using ART for up to 10 years. We assess outcomes of retention, adherence, maternal health, fertility intentions, and safety. Methods: This longitudinal, multicountry study (PROMOTE) enrolled women who initiated ART in an earlier perinatal clinical trial, PROMISE. PROMISE occurred from 2011 to 2016 and PROMOTE follow-up started in 2016 and is ongoing. The PROMOTE study was done at eight sites in four countries: Malawi (Blantyre and Lilongwe), South Africa (Durban and Soweto), Uganda (Kampala), and Zimbabwe (Harare, Seke North, and St Mary's). After baseline enrolment, women and their children are followed up every 6 months to collect information on medical history, antiretroviral therapy (ART) use, adherence, and health information, and to do physical examinations and laboratory tests. Obesity was defined as a body-mass index of 30 kg/m 2 or more. Data analyses were restricted to summaries of the main long-term outcomes (retention, adherence, maternal health, fertility intentions, and safety). We used descriptive and stratified analyses, and estimated rates using person-years of follow-up and computed probabilities based on Kaplan-Meier methods. Findings: PROMOTE enrolled 1987 mothers and 2522 children. The median follow-up time for mothers was 41·8 (IQR 35·8–42·0) months and for children was 35·7 (23·8–42·0) months. Overall retention rates were 96·5% for mothers and 94·3% for children at 12 months, and, at 42 months, were 88·9% for mothers and 85·4% for children. 1115 (89·1%) of 1252 women had an undetectable viral load at 42 months, which varied by site (81·7–93·8%). Reported maternal health improved over time, with the proportion of women with excellent to very good health increasing from 67·5% at baseline to 87·5% at 42 months, the proportion of unwell participants who visited a health centre declining from 14·7% to 2·8%, and the proportion of those admitted to hospital declining from 1·5% to 1·0%. The desire to have more children was consistently high at some sites. The proportion of women with obesity was high in South Africa and increased over time from 40·2% at baseline to 52·8% at 42 months. The overall pregnancy rate was 17·6 (95% CI 16·5–18·7) per 100 women-years, and mortality rates were 2·4 (1·4–3·9) per 1000 person-years for mothers and 3·4 (2·2–5·10) per 1000 person-years for children (0–9 years). Interpretation: The findings from this multicountry study are reassuring. These findings show that African women can consistently use ART for a long period after initiation, and long-term benefits can be maintained. Services to support maternal HIV care, treatment, and reproductive health should be strengthened. Funding: US President's Emergency Plan for AIDS Relief.